The impact of restrictive measures to prevent the spread of COVID-19 on students’ lifestyle - O.O. Vinogradov; O.I. Guzhva (Medičnì Perspektivi)
The need to develop effective strategies to overcome the social, economic, physiological and psychological consequences of the COVID-19 pandemic requires targeted research on the impact of restrictive measures on the lifestyle of people of different ages and socio-demographic groups, including youth, as the most able and active population. The article presents the assessment results of the peculiarities of the restrictive measures impact aimed at preventing the spread of acute respiratory disease COVID-19 on the territory of Ukraine on the lifestyle of student youth. The assessment of the general attitude of the respondents to the COVID-19 pandemic, as well as the peculiarities of the lifestyle before and after the introduction of restrictive measures, was conducted by interviewing students using a specially designed questionnaire. The survey involved 86 people (58.1% – women, 41.9% – men) aged 17 to 35. The majority of respondents (79.1%) were urban residents and had a household size ranging from 2 to 4 people (2.7±0.15 people). The results of the survey showed that the majority of students consider COVID-19 a dangerous infection (48.8%), feel anxiety / worry about their own health (58.1%) and the health of their loved ones (83.7%), support the establishment of quarantine (53.5%) and adhere to the recommended preventive measures (97.7%). The majority of students observe the statistics of COVID-19 in Ukraine (79.1%) and the world (81.4%). The most authoritative sources of information for the majority of respondents are official international (53.5%) and official Ukrainian sources (39.5%); however, a significant proportion of respondents also trust unofficial sources of information (23.3%). Most students do not adhere to the regime of self-isolation (51.2%), every day going outside their place of residence, daily contact with an average of 2.7±0.19 people. After the introduction of restrictive measures, the distribution of time for different types of activity has changed. There was a significant increase in time spent by students watching movies and TV series and a decrease in time for walking (p <0.05). The duration of sleep was not changed after the introduction of restrictive measures, however, the time frame of sleep shifted by about an hour – respondents began to fall asleep later on average and wake up later.